Montmorency tart cherry (Prunus cerasus L.) acts as a calorie restriction mimetic that increases intestinal fat and lifespan in Caenorhabditis elegans. (May 2020) - van de Klashorst, David; van den Elzen, Amber; Weeteling, Jasper; Roberts, Michael; Desai, Terun; Bottoms, Lindsay; Hughes, Samantha
Graphical abstract: Highlights: Montmorency tart cherries increases lifespan and fat content in low doses. MTC reduces pumping rate in C. elegans suggesting it acts as a calorific mimetic. MTC acts via the PPAR pathway in C. elegans, as it does in other systems. Low doses of MTC have a positive effect on healthy aging of C. elegans. Abstract: Montmorency Tart Cherries, MTC, ( Prunus cerasus L.) possess a high anthocyanin content as well as one of the highest oxygen radical absorbance capacities of fruits at common habitual portion sizes. MTC have been shown to contribute to reducing plasma lipids, plasma glucose and fat mass in rats and strikingly, similar effects are observed in humans. However, there is a paucity of research examining the molecular mechanisms by which such MTC effects are induced. Here, we show that when exposed to MTC, Caenorhabditis elegans display an extension of lifespan, with a corresponding increase in fat content and increase in neuromuscular function. Using RNA interference, we have confirmed that MTC is likely to function via the Peroxisome Proliferator-Activated Receptor (PPAR) signalling pathway. Further, consumption of MTC alters the pharyngeal pumping rate of worms which provides encouraging evidence that MTC may be operating as a calorie restriction mimetic via metabolic pathways.